2014
DOI: 10.1155/2014/308371
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Habitats in North East Germany: Reemergence of TBEV in Ticks after 15 Years of Inactivity

Abstract: The incidence of tick-borne encephalitis has risen in Europe since 1990 and the tick-borne encephalitis virus (TBEV) has been documented to be spreading into regions where it was not previously endemic. In Mecklenburg-West Pomerania, a federal state in Northern Germany, TBEV was not detectable in over 16,000 collected ticks between 1992 and 2004. Until 2004, the last human case of TBE in the region was reported in 1985. Following the occurrence of three autochthonous human cases of TBE after 2004, however, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Bavaria and Baden-Wuerttemberg) but sporadic cases were also reported from the upper north regions of the country, recently including Mecklenburg-Western Pomerania [26]. Signs of TBEV circulation in this area were also shown in 2007 by detection of TBEV RNA in I. ricinus ticks [28] and identification of anti-TBEV antibodies in small ruminants [30], and wildlife [29]. Even though we did not detect TBEV RNA in the collected ticks, several factors could contribute to a future expansion of the virus foci in Mecklenburg-Western Pomerania.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bavaria and Baden-Wuerttemberg) but sporadic cases were also reported from the upper north regions of the country, recently including Mecklenburg-Western Pomerania [26]. Signs of TBEV circulation in this area were also shown in 2007 by detection of TBEV RNA in I. ricinus ticks [28] and identification of anti-TBEV antibodies in small ruminants [30], and wildlife [29]. Even though we did not detect TBEV RNA in the collected ticks, several factors could contribute to a future expansion of the virus foci in Mecklenburg-Western Pomerania.…”
Section: Discussionmentioning
confidence: 93%
“…In 2004, the first autochthonous human case was registered after 19 years [27]. Furthermore, detection of TBEV in questing I. ricinus was found in 2007 for the first time since 1992 [28]. Later studies found anti-TBEV-IgG antibodies in wild game [29], sheep and goats [30].…”
mentioning
confidence: 99%
“…TBEV thus persists under a limited set of biotic and abiotic conditions. Some natural TBEV foci might be unstable over time when the conditions for TBEV persistence are not fulfilled anymore, but such instability has rarely been observed in the field [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the detection of new TBEV foci has been reported in Sweden (Haglund, 2002;Jaenson et al, 2012) and Norway (Csango et al, 2004;Haglund, 2002;Skarpaas et al, 2006Skarpaas et al, , 2004. There is evidence regarding the reactivation of old foci of TBEV, which for a long time (decades) have been inactive, thus turning the places into a risk area (Frimmel et al, 2014;Jääskeläinen et al, 2006;Kristiansen, 2002).…”
Section: Introductionmentioning
confidence: 99%